Shedding new light on the workings of motor proteins.
EU-funded scientists have captured the stiff-legged walk of a motor protein moving along an actin filament for the first time. Understanding how these proteins use energy to fuel biological tasks on a molecular level could lead to therapies for movement-related disorders.